sendo p (x)=2x^+5x-1,calcule a)p (3). b)p (-3)
emicosonia:
?????
Respostas
respondido por:
2
Sendo p (x)=2x^+5x-1,calcule a)p (3). b)p (-3)p(3)
x = 3
p(x) = 2x² + 5x - 1
p(3) = 2(3)² + 5(3) - 1
p(3) = 2(9) + 15 - 1
p(3) = 18 + 14
p(3) = 32
p(-3)
x = - 3
p(- 3) = 2(-3)² + 5(-3) - 1
p(-3) = 2(+9) - 15 - 1
p(-3) = + 18 - 16
p(-3) = 2
Quais os valores de a, b e c para que o polinômio g(x)=ax5+(b+3)x4+(c-5)x3 Seja nulo? pode responder essa pra mim ?
g(x) = ax⁵ + (b + 3)x⁴ + (c - 5)x³
SEJAM nulo:
ax⁵ + (b + 3)x⁴ + (c - 5)x³ = 0
a = 0
(b + 3) = 0
b + 3 = 0
b = - 3
(c - 5) = 0
c - 5 = 0
c = + 5
assim ( resposta)
a = 0
b = - 3
c = 5
x = 3
p(x) = 2x² + 5x - 1
p(3) = 2(3)² + 5(3) - 1
p(3) = 2(9) + 15 - 1
p(3) = 18 + 14
p(3) = 32
p(-3)
x = - 3
p(- 3) = 2(-3)² + 5(-3) - 1
p(-3) = 2(+9) - 15 - 1
p(-3) = + 18 - 16
p(-3) = 2
Quais os valores de a, b e c para que o polinômio g(x)=ax5+(b+3)x4+(c-5)x3 Seja nulo? pode responder essa pra mim ?
g(x) = ax⁵ + (b + 3)x⁴ + (c - 5)x³
SEJAM nulo:
ax⁵ + (b + 3)x⁴ + (c - 5)x³ = 0
a = 0
(b + 3) = 0
b + 3 = 0
b = - 3
(c - 5) = 0
c - 5 = 0
c = + 5
assim ( resposta)
a = 0
b = - 3
c = 5
ax⁵ + (b + 3)x⁴ + (c - 5)x³ = 0
a = 0
(b + 3) = 0
b + 3 = 0
b = - 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás